Evolutionary insights into Trm112-methyltransferase holoenzymes involved in translation between archaea and eukaryotes. Issue 16 (13th July 2018) - van Tran, Nhan; Muller, Leslie; Ross, Robert L; Lestini, Roxane; Létoquart, Juliette; Ulryck, Nathalie; Limbach, Patrick A; de Crécy-Lagard, Valérie; Cianférani, Sarah; Graille, Marc
Abstract: Protein synthesis is a complex and highly coordinated process requiring many different protein factors as well as various types of nucleic acids. All translation machinery components require multiple maturation events to be functional. These include post-transcriptional and post-translational modification steps and methylations are the most frequent among these events. In eukaryotes, Trm112, a small protein (COG2835) conserved in all three domains of life, interacts and activates four methyltransferases (Bud23, Trm9, Trm11 and Mtq2) that target different components of the translation machinery (rRNA, tRNAs, release factors). To clarify the function of Trm112 in archaea, we have characterized functionally and structurally its interaction network using Haloferax volcanii as model system. This led us to unravel that methyltransferases are also privileged Trm112 partners in archaea and that this Trm112 network is much more complex than anticipated from eukaryotic studies. Interestingly, among the identified enzymes, some are functionally orthologous to eukaryotic Trm112 partners, emphasizing again the similarity between eukaryotic and archaeal translation machineries. Other partners display some similarities with bacterial methyltransferases, suggesting that Trm112 is a general partner for methyltransferases in all living organisms.